A Family of Superhelicenes: Easily Tunable, Chiral Nanographenes by Merging Helicity with Planar π Systems - Reger,D; Haines,P; Amsharov,KY; Schmidt,JA; Ullrich,T; Bönisch,S; Hampel,F; Görling,A; Nelson,J; Jelfs,KE; Guldi,DM; Jux,N (Angewandte Chemie, 2021)
Abstract We designed a straightforward synthetic route towards a fullfledged family of πextended helicenes: superhelicenes. They have two hexaperihexabenzocoronenes (HBCs) in common that are connected via a central fivemembered ring. By means of structurally altering this 5membered ring, we realized a versatile library of molecular building blocks. Not only the superhelicene structure, but also their features are tuned with ease. Indepth physicochemical characterizations served as a proof of concept thereof. The superhelicene enantiomers were separated, their circular dichroism was measured in preliminary studies and concluded with an enantiomeric assignment. Our work was roundedoff by crystal structure analyses. Mixed stacks of M and Pisomers led to twisted molecular wires. Using such stacks, chargecarrier mobilities were calculated, giving reason to expect outstanding hole transporting properties.